(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2025)
The intimacy vs isolation phase is encountered by persons transitioning into early adulthood. During this stage, individuals desire to establish close and personal connections, with one of the chosen relationships being dating. An issue that frequently occurs is the utilization of violence. The objective of this study is to examine the role of assertiveness on the susceptibility of young adult women to experience dating violence. The sample size for this quantitative study was 150 partisipants, selected using the convenient sampling technique based on the following criteria: 1) Female; 2) Age between 18 and 35; 3) Residing in Jakarta; 4) Involvement in a heterosexual love relationship. In this study, two Likert measures were used: the Assertiveness Scale with 20 items and a reliability coefficient (α) of 0.873, and the Composite Abuse Scale (revised)-Short Form (CASR-SF) with 20 items and a reliability coefficient of 0.953. The regression test revealed a statistically significant negative effect between assertiveness and the tendency to experience dating violence among adult women in Jakarta. These findings suggest that persons who display higher levels of assertiveness are less likely to experience dating violence. It is suggested that future research will be able to explore various other variables that might influence dating violence on the relationship dynamics of early adult couples in Indonesia.